2011
DOI: 10.1016/j.electacta.2011.03.146
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistant TiO2 film formed on magnesium by liquid phase deposition treatment

Abstract: Liquid phase deposition treatment (LPD) was applied to form a corrosion protective titanium dioxide (TiO 2 ) film on commercially available pure magnesium. Changing the solution pH, from acidic to highly alkaline, and with the addition of sucrose, it becomes possible to form a highly adhesive and thin TiO 2 film on commercially available pure magnesium without any heat treatment. The role of the sucrose may be attributed to the formation of tetrafluoroboric acid (BF 4 ) -in the solution reducing the homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This is a condensed system with a short mean free path, and the change in internal free energy before and after the LPD reaction is relatively low. Hence, various metal oxide and/or hydroxide thin films can be prepared on different substrates, such as glass, metal, and polymers with complex surface morphologies, ,, simply by immersing the substrates in the LPD reaction solution. The LPD reaction proceeds spontaneously under ambient conditions and is the balance of two equilibrium reactions: hydrolysis (ligand-exchange) reaction of metal fluoride complexes (eq ) and the F – consumption reaction with boric acid or aluminum ions, which act as F – scavengers (eq or ). MF x ( x 2 n ) + normalH 2 normalO MO italicn + italicx normalF + 2 italicn normalH + where M represents Ti, Fe, Cu, Zr, Sn, W, Mo, V, Zr, Nb, and Ni, etc. normalH 3 BO 3 + 4 HF BF 4 + normalH 3 normalO + + 2 normalH 2 normalO Al 3 + + 6 HF normalH 3 AlF 6 <...…”
Section: Introductionmentioning
confidence: 99%
“…This is a condensed system with a short mean free path, and the change in internal free energy before and after the LPD reaction is relatively low. Hence, various metal oxide and/or hydroxide thin films can be prepared on different substrates, such as glass, metal, and polymers with complex surface morphologies, ,, simply by immersing the substrates in the LPD reaction solution. The LPD reaction proceeds spontaneously under ambient conditions and is the balance of two equilibrium reactions: hydrolysis (ligand-exchange) reaction of metal fluoride complexes (eq ) and the F – consumption reaction with boric acid or aluminum ions, which act as F – scavengers (eq or ). MF x ( x 2 n ) + normalH 2 normalO MO italicn + italicx normalF + 2 italicn normalH + where M represents Ti, Fe, Cu, Zr, Sn, W, Mo, V, Zr, Nb, and Ni, etc. normalH 3 BO 3 + 4 HF BF 4 + normalH 3 normalO + + 2 normalH 2 normalO Al 3 + + 6 HF normalH 3 AlF 6 <...…”
Section: Introductionmentioning
confidence: 99%
“…8 The capacity per unit weight of the active material therefore increases, and the battery capacity improves significantly. [9][10][11] Various methods for LDH synthesis, including hydrolysis reactions such as sol-gel and coprecipitation methods, have been reported. [12][13][14] However, the LDHs deposited by these methods have low crystallinities, and adhesion between the current collector and active material is poor.…”
Section: Introductionmentioning
confidence: 99%
“…reported fabrication of photo‐catalytic TiO 2 films on stainless steel . Some of the present authors reported corrosion‐resistant TiO 2 films formed on magnesium and also reported on the structure and chemical compositions of the films . Pourmand et al .…”
Section: Introductionmentioning
confidence: 55%